Advancements in Bamboo-Based Cushioning Material Manufacturing - Massaguni, Massriyady; Muhammad Irwan (INTEK: Jurnal Penelitian, 2024)
The study focuses on producing cushioning packaging material from bamboo fibers. The effects of varying the surface treatment duration and the proportions of foaming agents, adhesives, plasticizers, cross-linking agents, and other components were analyzed in terms of foam density, foaming rate, elasticity, and bubble size. The optimal reagents and the ideal ratios for the different components were identified. The parameters for the foaming process were determined based on a high-efficiency, eco-friendly foaming mechanism. Impact testing was conducted to obtain curves for maximum acceleration versus static stress, dynamic stress versus strain, and dynamic buffering factor versus stress. The study examined the dynamic buffering performance as a function of drop height and compared it to other cushioning materials. The findings indicate that at a height of 450 mm, the bamboo pulp product exhibited a lower peak acceleration value than EPE and EPS in the stress range of 2.8-5.4 kPa, indicating superior cushioning performance under these conditions.